Tri-Relasi Kompetensi sebagai “brand image” Pendidikan Nasional - Winarto Eka Wahyudi (Universitas Islam Lamongan, 2018)
Education runs very dynamically. Because they have to adjust to the pulse of changing times so rapidly, at least three urgent challenges must be answered by national education. The problem of advancing information technology, nationalism and socio-cultural spirit is a sexy issue that must not only be discussed but must also be answered thoroughly. In certain aspects, if education only responds to the progress of science and science, it will give birth to mechanical humans who are far from spiritual and cultural values. For this reason, in the millennial era, it is necessary to form a